Deepfake Disinformation By Political Buzzers: Analysis Of The Implications For Civil Liberties In The “Ibu Jilbab Pink” Case - Nailah Alifah Mujahidah; Lia Wulandari (UNIVERSITAS PAKUAN, 2026)
The increasing sophistication of digital media manipulation has intensified the spread of political disinformation, presenting new challenges for civil liberties in digital public spaces. This study examines the implications of deepfake disinformation about